Understanding of Employee Perspectives on Leadership, Communication, and Information Technology as Job Satisfaction Factors at the Langsa City DPR Secretariat - Harahap, Maslan; Sulastri, Sulastri; Harahap, Muhammad Yusuf; Siregar, Muhammad Noor; Nasution, Venty Desy Y; Juli Isnaini, Dewi Budhihartini (Mahesa Research Center, 2025)
This study aims to analyze the perspective of employees on leadership, communication, and information technology as factors that affect job satisfaction in the Langsa City DPR Secretariat. The research method used is qualitative with a descriptive approach. Data were obtained through in-depth interviews, observations, and document analysis, which were then analyzed using data reduction, categorization, and conclusion drawing techniques. The results of the study show that participatory leadership style has a positive impact on job satisfaction, especially when employees are involved in decision-making and given trust in carrying out their duties. In the aspect of communication, obstacles occur in the lack of clarity of direction from the leadership and the lack of feedback, although the relationship between employees is generally quite good. Meanwhile, the use of information technology is still limited due to inadequate facilities and lack of training. In conclusion, leadership, communication, and information technology are interrelated in influencing employee job satisfaction. The improvement of these three factors can create a more conducive, productive, and supportive work environment that supports employee welfare. These findings provide practical recommendations to improve human resource management in government organizations.